AN ANALYSIS OF THE RELATIONSHIP BETWEEN THE LIVES OF THE PRIMARY -SECONDARY SCHOOL STUDENTS REGARDING DOMESTIC VIOLENCE AT HOME AND THEIR ACADEMIC SUCCESS. - AYDIN, OKTAY (ELSEVIER SCIENCE BV, 2012)
The aim of this research is to analyze the relationship between domestic violence in the lives of 7th and 8th grade students and their academic success at school. This research was conducted at the Azmi Ertugrul Primary School in Pursaklar, Ankara/Turkey. Two questionnares, Personal Information Form and Family Life Scale, developed by the reseacher were used in this study. A total of 137 parents answered the questionnares and the academic success of the students was evaluated based on the 2011 National Exam Results (SBS). As the level of violence of mothers directed against their husbands increases, the level of their children's academic success was found to decrease. This finding suggests that the violent behaviours directed from fathers to mothers may be more socially acceptable and the children are psychologically affected negatively as a result of their mothers' violent behaviors against their fathers more than their fathers' violence against their mothers'. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of The Association of Science, Education and Technology
Keywords: domestic violence; academic success; violent behaviours; students; parents; SOCIAL SUPPORT; ACHIEVEMENT